Engineering and application of enzymes for lipid modification, an update. (July 2016) - Zorn, Katja; Oroz-Guinea, Isabel; Brundiek, Henrike; Bornscheuer, Uwe T.
Abstract: This review first provides a brief introduction into the most important tools and strategies for protein engineering ( i.e. directed evolution and rational protein design combined with high-throughput screening methods) followed by examples from literature, in which enzymes have been optimized for biocatalytic applications. This covers engineered lipases with altered fatty acid chain length selectivity, fatty acid specificity and improved performance in esterification reactions. Furthermore, recent achievements reported for phospholipases, lipoxygenases, P450 monooxygenases, decarboxylating enzymes, fatty acid hydratases and the use of enzymes in cascade reactions are treated.